Reconsidering terms for mechanisms of polymer growth: the "step-growth" and "chain-growth" dilemma. Issue 16 (5th April 2022) - Chan, Chin Han; Chen, Jiun-Tai; Farrell, Wesley S.; Fellows, Christopher M.; Keddie, Daniel J.; Luscombe, Christine K.; Matson, John B.; Merna, Jan; Moad, Graeme; Russell, Gregory T.; Théato, Patrick; Topham, Paul D.; et al.
Abstract : Terms used for mechanisms of polymer growth are varied and problematic; we detail here our concerns with the terms "step-growth" and "chain-growth." Ultimately, we seek terms that are simple, accurate, and attractive to the polymer community. Abstract : The terms "step-growth polymerization" and "chain-growth polymerization" are used widely in both written and oral communications to describe the two main mechanisms of polymer growth. As members of the Subcommittee on Polymer Terminology (SPT) in the Polymer Division of the International Union of Pure and Applied Chemistry (IUPAC), we are concerned that these terms are confusing because they do not describe the fundamental differences in the growth of polymers by these methods. For example, both polymerization methods are comprised of a series of steps, and both produce polymer chains. In an effort to recommend comprehensive terms, a 1994 IUPAC Recommendation from the then version of SPT suggested polycondensation and polyaddition as terms for the two variants of "step-growth polymerization", and similarly chain polymerization and condensative chain polymerization for the two variants of "chain-growth polymerization". However, these terms also have shortcomings. Adding to the confusion, we have identified a wide variety of other terms that are used in textbooks for describing these basic methods of synthesizing polymers from monomers. Beyond these issues with "step-growth" and "chain-growth", synthesis of polymers one monomer unit at a time presents a related dilemma in that this synthetic strategy is wholly encompassed by neither of the traditional growth mechanisms. One component of the mission of IUPAC is to develop tools for the clear communication of chemical knowledge around the world, of which recommending definitions for terms is an important element. Here we do not endorse specific terms or recommend new ones; instead, we aim to convey our concerns with the basic terms typically used for classifying methods of polymer synthesis, and in this context we welcome dialogue from the broader polymer community in a bid to resolve these issues.